Penerapan Model Problem Based Learning sebagai Solusi Mengatasi Problematika Guru Mata Pelajaran Al Quran Hadits di MTs DDI Manding Kecamatan Polewali Kabupaten Polewali Mandar - Sutraningsih (Jurnal Ilmiah Tarbiyah Umat, 2022)
The purpose of this study is to describe the problems of teachers of Al - Qur'an Hadith subjects and to describe the application of the Problem Based Learning model as a soluti on to overcome teacher problems at MTs DDI Manding, Polewali District, Polewali Mandar Regency. This type of research is a case study with a qualitative method whose data and research locations are located at MTs DDI Manding. The informant/Key person of th is study amounted to 1 person, namely the teacher of the Qur'an Hadith subject. The methods used in this research are: Observation, Interview and Documentation. Data analysis techniques in this study are data reduction, data presentation, and conclusion dr awing, to hold the validity of the data in this study, namely the extension of participation, persistence of observation, and triangulation. While the criteria of dependence and certainty using auditing techniques. The results showed that the problems of t he teacher of Al - Qur'an hadith subjects at MTs DDI Manding include: comparison of suitability between materials, learning devices and students, time factor, social media, problems reading Al - Qur'an verses and problems understanding. As for how to overcome the problems of the Al - Qur'an Hadith teacher at MTs DDI Manding as a solution that the teacher does is 1) implement the PBL (Problem Based Learning) Model, 2) optimize the available time, 3) confiscate cellphones during learning, 4) provide BTA extracurric ular activities, 5) provide specific tasks for reading Arabic script, and 6) Conduct group guidance in class.